Root-knot nematode Meloidogyne incognita induced changes in morpho-anatomy and antioxidant enzymes activities in Trachyspermum ammi (L.) plant: A microscopic observation. (December 2021) - Danish, Mohammad; Robab, Merajul Islam; Marraiki, Najat; Shahid, Mohammad; Zaghloul, Nouf S.S.; Nishat, Yasar; Shaikh, Hisamuddin
Abstract: Phytopathogens including nematodes cause extreme yield misfortunes in agricultural practices. Considering these threatening problems, present study was conducted to assess the effect of different inoculums levels (100J2, 500J2, 1000J2, 2000J2, 4000J2 ) of Meloidogyne incognita in Trachyspermum ammi (L.) plants cultivated under glass-house condition. As the degrees of inoculums expanded, plant growth, biomass, yield attributes and seed oil content were significantly ( p ≤ 0.05) diminished. Furthermore, the activities of antioxidant enzyme such as peroxidase (POD), catalase (CAT), superoxide dismutase (SOD) and ascorbate peroxidase (APX) were increased with the increasing inoculum levels. Additionally, to examine the infection and cyto-anatomical changes in the roots tissues of T . ammi after exposure to M. incognita, roots samples were longitudinally (LS) and transitionally (TS) sectioned, stained with dye and observed under magnifying lens. Critical irregularities in primary and secondary roots were examined after nematode feeding inside the roots. Second stage juveniles (J2 ) of M. incognita entered into inter and intracellular region of developing roots and their branches. The main indication of disease was observed as hypertrophy in cells around the top of the nematode head. Cytological changes in hypertrophied cells were turned out to be more conspicuous with increment in inoculum level, and cells changed into discrete giant cells. Hypertrophy (huge and contained thick and granular cytoplasm) and hyperplasia in root tissue close to nematode head had quick reaction. Additionally, sieve tube components of the phloem, close to giant cells were more limited and looked like with close to parenchyma cells. At Higher degree of nematode inoculums, egg masses were found related with every single developed female. Tissues were disturbed as the egg masses were pushed out to surface of the root. From this investigation, it very well may be deduced that change in cells of rankled tissue was basic for the food of giant cells and for endurance of the nematode. Highlights: Trachyspermum ammi L. was inoculated with varying inoculum level of Root-knot nematode Meloidogyne incognita to observe host-parasite relationship. M. incognita altered the physico-chemical characteristics, antioxidant enzymes, yield and nematode related parameters in T. ammi . Significant anatomical changes in infected plant roots were observed. M. incognita developed giant cell and giant cell complexes which caused diversion of photosynthetic material towards infection sites. ✓Hypertrophied in cortical region, abnormal xylem and phloem was clear observed in nematode infected roots.